2015
DOI: 10.1098/rstb.2015.0020
|View full text |Cite
|
Sign up to set email alerts
|

Type III secretion systems: the bacterial flagellum and the injectisome

Abstract: One contribution of 12 to a theme issue 'The bacterial cell envelope'. The flagellum and the injectisome are two of the most complex and fascinating bacterial nanomachines. At their core, they share a type III secretion system (T3SS), a transmembrane export complex that forms the extracellular appendages, the flagellar filament and the injectisome needle. Recent advances, combining structural biology, cryo-electron tomography, molecular genetics, in vivo imaging, bioinformatics and biophysics, have greatly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
181
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(187 citation statements)
references
References 272 publications
(393 reference statements)
1
181
0
5
Order By: Relevance
“…Salmonella pathogenicity island 1 (SPI1) and Shigella T3SA belong to the Inv/Mxi-Spa family of T3SS (25), and accordingly, their proteins share a moderate degree of sequence similarity. Interestingly, although most Salmonella enterica serovar Typhimurium (Salmonella) reside within phagosomes, a significant number of Salmonella (∼15-20%) escape from nascent vacuoles to establish an intracytoplasmic replicative niche in epithelial cells in a SPI1 T3SS-dependent manner (15,26).…”
Section: A Single Component Of the Translocon Apparatus Mediates Phagmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonella pathogenicity island 1 (SPI1) and Shigella T3SA belong to the Inv/Mxi-Spa family of T3SS (25), and accordingly, their proteins share a moderate degree of sequence similarity. Interestingly, although most Salmonella enterica serovar Typhimurium (Salmonella) reside within phagosomes, a significant number of Salmonella (∼15-20%) escape from nascent vacuoles to establish an intracytoplasmic replicative niche in epithelial cells in a SPI1 T3SS-dependent manner (15,26).…”
Section: A Single Component Of the Translocon Apparatus Mediates Phagmentioning
confidence: 99%
“…T3SSs have been divided into eight distinct families based on phylogenetic analyses (25). The Salmonella SPI1 and Shigella Mxi-Spa systems are the best characterized members of the Inv/Mxi-Spa family, which also includes T3SSs from Chromobacterium (Cpi-1), Yersinia (Ysa), and Burkholderia (Bsa).…”
Section: A Single Component Of the Translocon Apparatus Mediates Phagmentioning
confidence: 99%
“…A recent phylogenetic analysis revealed that the injectisome originated from an ancient flagellar system by an exaptation process, i.e., recruiting core components from a rotary engine used for bacterial propulsion into a machine employed for interkingdom protein transport (38). Among the components of these machineries that preserve an evolutionary footprint in their sequences are the export apparatus proteins EscR, EscS, EscT, EscU, and EscV (FliP, FliQ, FliR, FlhB, and FlhA, respectively, in the flagellum), the inner membrane ring protein EscJ (FliF), the cytosolic ATPase complex components EscL and EscN (FliH and FliI), and the C-ring major component EscQ (FliM and FliN) (39).…”
mentioning
confidence: 99%
“…flagellum | chaperones | assembly factors | NMR spectroscopy | type III secretion T he flagellum is the organelle that enables bacterial locomotion and is one of the most sophisticated protein machines (1)(2)(3)(4). Flagella organelles may act as virulence factors because motility is crucial for the action of pathogenic bacteria (5,6).…”
mentioning
confidence: 99%